Pedagodzy – zasłużeni dla zachowania tożsamości narodowej Polaków na uchodźstwie po II wojnie światowej (na przykładzie organizacji Polska Macierz Szkolna) - Zamecka-Zalas, Olga (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2017)
The article presents the profiles of distinguished educationalists, who stressed the importance of national identity among Poles in exile. As a result, they contributed to maintain Polish identity in emigration families, especially to patriotic and religion education of young Polish generation.
Keywords: education; educationalist; emigration; exile; family; national identity; patriotic; religion education